Chapter 15 La medicina predittiva e il dibattito etico sui test genetici - Manzini, Arianna (FrancoAngeli, 2019)
The "genetic revolution" that characterized the beginning of the third millennium and the most recent "genomic revolution" have made me wait more and more of human existence have become the object of scientific and technological control. This has created great expectations regarding the diagnostic potential and therapeutics in this field; however, to the increased ability to control there is an increasing number of situations that pose serious dilemmas moral standards for researchers, doctors and patients. In the following reflections we will focus our attention on the issues bioethics related to the management of the diagnostic potential expressed by genetic tests. The first part will be dedicated to a brief overview of the state of the art genetic testing from a scientific point of view; the second part will deal with the ethical debate around their uses. The goal we set ourselves, integrating our competences, respectively biological and bioethical ones, is to allow you to acquire an overview of the main guidelines that confront each other in the current bioethical debate, in order to elaborate in our pluralistic context of an adequate ethical-regulatory framework.